Environmental change and enteric zoonoses in New Zealand: a systematic review of the evidence. (12th October 2014) - Lal, Aparna; Lill, Adrian W.T.; Mcintyre, Mary; Hales, Simon; Baker, Michael G.; French, Nigel P.
Abstract: Objective : To review the available evidence that examines the association between climatic and agricultural land use factors and the risks of enteric zoonoses in humans and consider information needs and possible pathways of intervention. Methods: The electronic databases PubMed, Web of Science and Embase and government websites were searched systematically for published literature that investigated the association of climatic and/or agricultural exposures with the incidence of the four most common enteric zoonotic diseases in New Zealand (campylobacteriosis, salmonellosis, cryptosporidiosis and giardiasis). Results The 16 studies in the review demonstrated significant associations between climate, agricultural land use and enteric disease occurrence. The evidence suggests that enteric disease risk from environmental reservoirs is pathogen specific. In some rural regions, environmental pathogen load is considerable, with multiple opportunities for zoonotic transmission. Conclusions: Enteric disease occurrence in NZ is associated with climate variability and agricultural land use. However, these relationships interact with demographic factors to influence disease patterns. Implications: Improved understanding of how environmental and social factors interact can inform effective public health interventions under scenarios of projected environmental change.